Blue Jeans, Chewing Gum and Climate Change Litigation: American Exports to Europe - Hare, Daniel G (Utrecht Journal of International and European Law, 2013)
This paper analyses how American-style climate change litigation might be adopted by the European Union ('EU') and projects potential methods by which the EU might employ the US model, if it indeed chooses to take the climate change battle to the courts. By synthesising existing US case law in the environment and climate change fields, the paper roughly defines the 'American model' of climate change litigation as parens patriae actions, oftentimes based in the tort of public nuisance, brought by states and other sovereign entities against polluter-defendants. The structural differences between the common law United States and the predominantly civil law European Union are substantial, and the EU has traditionally been averse to enter too far into the American mass torts arena. Accordingly, Europeans have not yet undertaken these types of lawsuits. This paper identifies and examines several realistic options for Europe's possible espousal of the American climate change litigation model through EU law and national law of individual Member States. Although the comparison is admittedly imperfect, I conclude that by drawing on the blueprint of its American counterparts, the EU could viably use Directive 2004/35/EC (environmental liability with regard to the prevention and remedying of environmental damage and the 'polluter pays' principle) and Directive 2003/87/EC (establishing a scheme for greenhouse gas emission allowance trading) in a parens patriae-like manner to hold defendants liable for damages caused by climate change. Additionally with case studies focusing on France, Germany and the United Kingdom, national law alternatives exist for individual Member States, as well as regional and local governments, to take action on behalf of their citizens for injuries resulting from climate change, just like sovereign bodies in the United States have done.